Contract as promise : a theory of contractual obligation - Fried, Charles, 1935- (New York : Oxford University Press, 2015)
'Contract as Promise' is a study of the foundations and structure of contract law. It has both theoretical and pedagogic purposes. It moves from trust to promise to the nuts and bolts of contract law. The author shows that contract law has an underlying unifying moral and practical structure. This second edition retains the original text, and includes a new Preface. It also includes a lengthy postscript that takes account of scholarly and practical developments in the field over the last thirty years, especially the large and rich law and economics literature.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on April 21, 2015).
Keywords: Contracts; Promise (Law)